2004
DOI: 10.1093/carcin/bgh275
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TP53, but not FGFR3, in urothelial cell carcinoma of the bladder are influenced by smoking: contribution of exogenous versus endogenous carcinogens

Abstract: Smoking is a major risk factor for urothelial cell carcinoma of the bladder (UCC). Mutations in the FGFR3 and TP53 genes have been shown to define two distinct pathways in superficial papillary and invasive UCC disease, respectively. We investigated the relationship between smoking and these mutations by means of denaturing high performance liquid chromatography and sequencing for 110 primary UCC of the bladder. This study included 48 current smokers, 31 ex-smokers and 31 non-smokers. Thirty-five of the tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 41 publications
3
61
1
1
Order By: Relevance
“…FGFR3 mutations were studied with the SNaPshot method (29). TP53 (exons 2-11), KRAS (exons 2-3), NRAS (exons 2-3), HRAS (exons 2-3) and PIK3CA (exons 2, 9, and 20) gene mutations were screened by direct sequencing with previously described primers and protocols (30,31), available on request. All mutations were confirmed by sequencing both strands of a second, independent PCR product.…”
Section: Data Production and Analysismentioning
confidence: 99%
“…FGFR3 mutations were studied with the SNaPshot method (29). TP53 (exons 2-11), KRAS (exons 2-3), NRAS (exons 2-3), HRAS (exons 2-3) and PIK3CA (exons 2, 9, and 20) gene mutations were screened by direct sequencing with previously described primers and protocols (30,31), available on request. All mutations were confirmed by sequencing both strands of a second, independent PCR product.…”
Section: Data Production and Analysismentioning
confidence: 99%
“…Of the 63 reports selected for detailed evaluation, 33 were excluded as duplications or because they lacked key data. The final meta-analysis was carried out on the remaining 30 studies (Billerey et al, 2001;Kimura et al, 2001;Bakkar et al, 2003;Rieger-Christ et al, 2003;van Rhijn et al, 2003van Rhijn et al, , 2004Hernández et al, 2005;Jebar et al, 2005;van der Aa et al, 2005;Wallerand et al, 2005;Hernández et al, 2006;Lindgren et al, 2006;Tomlinson et al, 2007;van Oers et al, 2007;Burger et al, 2008;Junker et al, 2008;Eltze et al, 2009;Ouerhani et al, 2009;van Oers et al, 2009;Zieger et al, 2009;Bakkar et al, 2010;Bodoor et al, 2010;Kompier et al, 2010;Miyake et al, 2010;van Rhijn et al, 2010;Al-Ahmadie et al, 2011;Dodurga et al, 2011;Serizawa et al, 2011;Sjödahl et al, 2011;van Rhijn et al, 2012). Twenty-five of the studies (Table 1A) investigated the association between FGFR3 mutations and grade or stage, while the other 13 studies (Table 1B) investigated the prognostic value of FGFR3 mutations for BC.…”
Section: Resultsmentioning
confidence: 99%
“…Tobacco smoking has been established a major risk factor for bladder cancer because many carcinogens present in tobacco alter gene expression and damage DNA (Wallerand et al, 2005;Volanis et al, 2010). A metaanalysis summarizing the epidemiology of urinary tract cancer risk and cigarette smoking observed that current smokers have an approximately threefold higher risk than non-smokers (Zeegers et al, 2000).…”
Section: Discussionmentioning
confidence: 99%